Strategy as practice used in recognition of a graduate course by MEC - Roncon, Aleksander; Sousa, Tarcita Cabral Ghizoni de; Beltrame, Indiara; Lavarda, Rosália Aldraci Barbosa (Revista de Administração da UFSM, 2013)
DOI: 10.5902/198346598850 The strategizing is a theoretical approach that includes the implementation of strategies by connecting the practice performed by practitioners who have types of behaviors driven by social practices (Jarzabkowski et al., 2007). The aim of this study was to determine how the strategy is developed in practice for the recognition of an undergraduate degree at MEC. For both: (i) identify the strategic practices adopted in the organization, (ii) verify how the practice happens at different organizational levels and (iii) analyze how practitioners participating in the strategy as practice. The research approach is qualitative. The study was conducted in a private college of character located in northern Paraná. We used a semi-structured interview structured with open questions, document analysis and observation, and data collection techniques, providing triangulation of data collected. For the data analysis we adopted the technique Exam Pattern of Behavior (PÉREZ-AGUIAR, 1999). The results highlight the need for alignment between the three elements developed in the work Jarzabkowski et al. (2007), and emphasize the existence of the axis of environmental management across the entire line as pedagogical courses offered, as a requirement of MEC.